2015
DOI: 10.5935/0100-4042.20150050
|View full text |Cite
|
Sign up to set email alerts
|

DEVELOPMENT AND VALIDATION OF A HPLC-PDA METHOD AND PRELIMINARY STABILITY STUDY OF SYNEPHRINE INCitrus aurantium L.DRY EXTRACT

Abstract: A reversed-phase liquid chromatographic method was developed for the assay of synephrine in Citrus aurantium dry extract. The chromatographic separation used a C18 (250 × 4.6 mm, 5 µm) column and a mobile phase consisting of acetonitrile: 0.01% orthophosphoric acid (pH 3.0) at a 15:85 ratio, flow rate of 1 mL min -1 and detection at 220 nm. The detector response was linear in the range 15 - 45 mg mL -1 . Specificity and stability, indicating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…There are no indications that p ‐synephrine adversely affects the heart, liver, kidneys, or thyroid at doses up to 100 mg per day (Stohs et al ., ; Kaats et al ., ; Shara et al ., ; Kaats and Stohs, ), and as a consequence, there is no evidence supporting the proposed contraindications. Furthermore, studies have shown that no teratogenicity (Hansen et al ., ) or mutagenicity (Morimoto et al ., ; Kaefer, ; Deshmukh et al ., ) occurs in response to p ‐synephrine and bitter orange extracts. However, some cautionary statements regarding use of bitter orange extract and p ‐synephrine may be warranted and are subject to further discussions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no indications that p ‐synephrine adversely affects the heart, liver, kidneys, or thyroid at doses up to 100 mg per day (Stohs et al ., ; Kaats et al ., ; Shara et al ., ; Kaats and Stohs, ), and as a consequence, there is no evidence supporting the proposed contraindications. Furthermore, studies have shown that no teratogenicity (Hansen et al ., ) or mutagenicity (Morimoto et al ., ; Kaefer, ; Deshmukh et al ., ) occurs in response to p ‐synephrine and bitter orange extracts. However, some cautionary statements regarding use of bitter orange extract and p ‐synephrine may be warranted and are subject to further discussions.…”
Section: Discussionmentioning
confidence: 99%
“…In another study published only in thesis form (Kaefer, ), p ‐synephrine and its forced degradation products were studied for their potential mutagenic effects. Degradation of p ‐synephrine was produced under acidic, basic, oxidative, and proteolytic conditions.…”
Section: Mutagenicity Studiesmentioning
confidence: 99%
“…Therefore, it is important to establish an approach for detecting synephrine in feed. Many existing detection methods for synephrine have been presented, including TLC scanning , CE , GC–MS , LC , and HPLC–MS . In our study, a novel sample pretreatment method based on internal standards combined with UHPLC–MS/MS was developed to determine the level of synephrine in feeds.…”
Section: Introductionmentioning
confidence: 99%